Imogolite Synthetized in Presence of As(Iii) Induces Low Cell Toxicity and Hemolysis, in Vitro, Potential Stabilization of Arsenite Present in Aqueous Systems - Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (American Chemical Society, 2019)
Imogolite is a nanotubular aluminosilicate that has low toxicity in biological systems and due to its morphological and surface properties has a growing interest in environmental applications and biomedical areas. Its synthesis is highly sensitive to the presence of other ions, being able to inhibit or retard the process of imogolite formation, which could change the cytotoxic response of this substrate, something scarcely reported in the literature. In this context, the presence of arsenite during the synthesis of imogolite caused significant changes in the dimensions and surface behavior of these nanotubes. Cell viability was evaluated on EA.hy926 and HepG2 cells by (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide) assay at 24 h. Meanwhile, the potential effects on human red blood cells, namely, hemolysis and morphological changes, were determined at 0 and 24 h. The range of % As tested of the nanotube showed cell toxicity similar to the control condition. Similarly, the As-based nanotubes induced hemolysis similar to controls and slight morphological changes of red blood cells at 0 and 24 h of exposition. These results indicate that As-based imogolite-like nanotubes are not toxic nor hemolytic and can be potentially used in processes like water purification. © 2019 American Chemical Society.